2017
DOI: 10.1103/physreve.95.042119
|View full text |Cite
|
Sign up to set email alerts
|

Generalized balance equations for charged particle transport via localized and delocalized states: Mobility, generalized Einstein relations, and fractional transport

Abstract: A generalised phase-space kinetic Boltzmann equation for highly non-equilibrium charged particle transport via localised and delocalised states is used to develop continuity, momentum and energy balance equations, accounting explicitly for scattering, trapping/detrapping and recombination loss processes. Analytic expressions detail the effect of these microscopic processes on the mobility and diffusivity. Generalised Einstein relations (GER) are developed that enable the anisotropic nature of diffusion to be d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“… 24 . This would allow for the derivation of a skewness analogue of Einstein’s relation that would also take into account the field dependence of mobility 24 . This may also shed light on the recent results of Petrović et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 24 . This would allow for the derivation of a skewness analogue of Einstein’s relation that would also take into account the field dependence of mobility 24 . This may also shed light on the recent results of Petrović et al .…”
Section: Discussionmentioning
confidence: 99%
“…( 1 ) has an enhanced diffusivity in the direction of the field due to trapping and detrapping. This enhancement manifests as the following generalised Einstein relation 24 …”
Section: Relating Skewness Mobility and Temperaturementioning
confidence: 98%
See 2 more Smart Citations
“…It was shown that with particular choices of the trapping operator the fractional diffusion equation could be obtained from appropriate integrations and, when applied to organic semiconductor transport, the appropriate short and longtime behaviour was obtained, validating the approach [13,14]. This model was subsequently extended to include energy-dependent collision, trapping and loss rates, analysed using momentum transfer theory and used to generalise classical relations such as the Wannier and Einstein relations [16,17].…”
Section: Introductionmentioning
confidence: 98%